2012
DOI: 10.1038/onc.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

TIP30 loss enhances cytoplasmic and nuclear EGFR signaling and promotes lung adenocarcinogenesis in mice

Abstract: Lung adenocarcinoma, the most common type of human non-small cell lung cancer (NSCLC), frequently overexpresses EGFR. However, the mechanisms underlying EGFR overexpression are not completely understood. Recent studies have identified that decreased expression of TIP30 is associated with the metastasis of human NSCLCs, but a causative relationship between TIP30 deficiency and NSCLC development remains unclear. We show here that Tip30 deletion leads to spontaneous development of lung adenomas and adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…Both LN(AI) and LN95 cells are derived from LNCaP cells, but have been cultured under long-term ADT conditions, thus possessing an ADT-resistant phenotype. Using an absolute quantification method, real-time qPCR showed that VCaP cells expressed AR RNA that was 5-10 fold higher than LNCaP and LNCaP derived cells (Fig.1 and Suppl.1A), consistent with the report that VCaP cells have an increased AR gene copy number (35). AR RNA level was ~17.9 fold higher than AR-V7 in VCaP cells.…”
Section: Resultssupporting
confidence: 88%
“…Both LN(AI) and LN95 cells are derived from LNCaP cells, but have been cultured under long-term ADT conditions, thus possessing an ADT-resistant phenotype. Using an absolute quantification method, real-time qPCR showed that VCaP cells expressed AR RNA that was 5-10 fold higher than LNCaP and LNCaP derived cells (Fig.1 and Suppl.1A), consistent with the report that VCaP cells have an increased AR gene copy number (35). AR RNA level was ~17.9 fold higher than AR-V7 in VCaP cells.…”
Section: Resultssupporting
confidence: 88%
“…We have previously demonstrated that the expression level of cyclin D1 was significantly increased in a mouse TIP30 knock-out model [18]. In our current study, we used qRT-PCR to confirm that TIP30 regulates cyclin D1 transcription.…”
Section: Tip30 Knockdown Upregulates Cyclin D1 Mrna Expression and Cesupporting
confidence: 57%
“…Our previous study showed that lung adenomas and adenocarcinomas developed spontaneously in Tip30 knock-out mice, and that the loss of TIP30 function caused the upregulation of EGFR downstream signaling targets in pulmonary cells, including EGFR, p-Akt, and p-Erk1/2. We also showed that TIP30 knockdown in human lung adenocarcinoma cells delayed EGFR degradation, and increased EGFR nuclear localization [18]. These findings suggest that EGF/EGFR signaling pathways may be involved in the role of TIP30 in lung adenocarcinomas.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies have demonstrated that the nuclear import of EGFR and the signal cascade induced by nuclear EGFR had pivotal roles in the malignant proliferation and survival of certain types of tumor tissues (35)(36)(37). Immunohistochemical analysis of breast tumor tissues revealed that EGFR expression levels in the nucleus are positively correlated with the expression of Ki-67, a biomarker of cell proliferation, and negatively correlated with the survival rate (38,39).…”
Section: Discussionmentioning
confidence: 99%